Psychological distress on online learning during the pandemic COVID-19 among undergraduate students at school of health sciences, Universiti Sains Malaysia - Sayuti, Nurhayati (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Psychological distress of university students has become increasingly vital since online learning becomes the first platform for delivering education as the COVID-19 crisis has interrupted the common learning process of students. A cross-sectional study was conducted on 409 participants. Self-administered questionnaire was given to the participants that fit the inclusion criteria via online platform. The general objective of this study is to assess the psychological distress on online learning during the pandemic COVID-19 among undergraduate students at the School of Health Sciences, USM. The data was analyzed by descriptive statistics and Chi-Square test by using Statistical Package of Social Sciences (SPSS) 26.0. The mean level of psychological distress in this study is 1.17 (SD 0.434) and the mean of barriers to online learning are 2.49 (SD 0.780), 2.25 (SD 0.711), 1.85 (SD 0.827), 2.24 (SD 0.752), 2.00 (SD 0.673), 1.13 (SD 0.423), 1.86 (SD 0.952), 2.32 (SD 0.931), 1.32 (SD 0.659) and 1.10 (SD 0.348). Most of the participants have a normal range of psychological distress 347 (84.8%) with only 53 (13.0%) experienced mild to moderate anxiety levels and only nine (2.2%) experienced marked to severe anxiety levels. Chi-Square test revealed there is a statistically significant association between level of psychological distress on online learning and barriers to online learning on (inability to adjust learning style, mental health difficulties, poor communication or lack of clear direction from educators, unreliable or no internet access, limited physical space conducive to studying, need to fulfill responsibilities at home, need to work for extra incomes, lack of basic needs). However, there is no statistically significant association between level of psychological distress on online learning and barriers to online learning on (lack of technical skills and no smartphone or computer, or limited access due to gadget sharing with others). Besides, there is no statistically significant association between socio-demographic data (gender, age, ethnicity, field of study, year of field, current accommodation) and level of psychological distress on online learning